2013
DOI: 10.1590/s0102-86502013001200007
|View full text |Cite
|
Sign up to set email alerts
|

Expression of oxidative stress and antioxidant defense genes in the kidney of inbred mice after intestinal ischemia and reperfusion

Abstract: PURPOSE:To determine the gene expressions profile related to the oxidative stress and the antioxidant response in the kidneys of mice subjected to intestinal ischemia and reperfusion. METHODS:Twelve inbred mice (C57BL/6) were randomly assigned to one of two groups: the control group (CG) underwent anesthesia and was observed for 120 min and the ischemia/reperfusion group (IRG), animals were anesthetized and subjected to laparotomy and ischemia for 60 minutes followed by 60 minutes of reperfusion. The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Superoxide dismutase 2 (SOD2), which converts superoxide anions to hydrogen peroxide and oxygen, is specific for mitochondria 30 . Moreover, the transcription of genes encoding antioxidant enzymes, such as SOD2, catalase and glutathione peroxidase, is activated by nuclear factor erythroid 2-related factor 2 (NRF2) in response to oxidative stress, providing a mechanism to prevent excessive ROS production 31 . The importance of these antioxidant systems is to maintain optimal ATP production and sustain mitochondrial function.…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Superoxide dismutase 2 (SOD2), which converts superoxide anions to hydrogen peroxide and oxygen, is specific for mitochondria 30 . Moreover, the transcription of genes encoding antioxidant enzymes, such as SOD2, catalase and glutathione peroxidase, is activated by nuclear factor erythroid 2-related factor 2 (NRF2) in response to oxidative stress, providing a mechanism to prevent excessive ROS production 31 . The importance of these antioxidant systems is to maintain optimal ATP production and sustain mitochondrial function.…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…The lncRNA NONRATT006517.2, TCONS_00022796, NONRATT020511.2 and TCONS_00006475 were predicted to act on Xirp1 in a trans fashion. Xirp1 is an oxidative stress and antioxidant defense gene, and its expression increased in renal tissue under ischemia and reperfusion injury [ 22 ]. Xirp1 is a newly identified vitamin D receptor interacting protein and has an influence on VDR activity in the heart [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 37 genes in the intestine and 2 genes in the lung were hyperexpressed. These numbers, which are quite different, seem reasonable because ischemia and reperfusion injury in the bowel is expected to be much more severe in local 8 tissue than in distant tissues [9][10][11] . Moreover, in the lung tissue a peculiarity occurs: oxygen reaches the alveoli by two routes, perfusion and ventilation.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Acta Cir Bras. 2018;33(5):462-471 in local organs 8 and in organs distant from ischemia 9,10 , allowing a better understanding of the various aspects of this phenomenon in the diagnosis, monitoring and treatment of ischemic disease.…”
mentioning
confidence: 99%